Chemical composition and evaluation of modulatory of the antibiotic activity from extract and essential oil of Myracrodruon urundeuva. (May 2014) - Figueredo, Fernando G.; Lucena, Bruno F. F.; Tintino, Saulo R.; Matias, Edinardo F. F.; Leite, Nadghia F.; Andrade, Jacqueline C.; Nogueira, Lavouisier F. B.; Morais, Edson C.; Costa, José G. M.; Coutinho, Henrique D. M.; Rodrigues, Fabiola F. G.
Abstract Context: The combination of antibiotics with natural products has demonstrated promising synergistic effects in several therapeutic studies. Objective: The aim of this study was to determine the effect of a combination of an ethanol extract of Myracrodruon urundeuva Fr. All. (Anacardiaceae) (aroeira plant) and its essential oil with six antimicrobial drugs against multiresistant strains of Staphylococcus aureus and Escherichia coli from clinical isolates. Materials and methods: After identification of the chemical components by GC-MS, the antibacterial activity of the natural products and antibiotics was assessed by determining the minimal inhibitory concentration (MIC) using the microdilution method and concentrations ranging 8–512 μg/mL and 0.0012–2.5 mg/mL, respectively. Assays were performed to test for a possible synergistic action between the plant products and the antimicrobials, using the extract and the oil at a sub-inhibitory concentration (128 μg/mL) and antibiotic at concentrations varying between 8 and 512 μg/mL. Results: The GC-MS analysis identified the main compound as δ-carene (80.41%). The MIC of the natural products was >1024 μg/mL, except against S. aureus ATCC25923. Only the combinations of the natural products with gentamicin, amikacin and clindamycin were effective against S. aureus 358, enhancing the antibiotic activity by reducing the MIC. Conclusions: The extract from aroeira showed a higher antibacterial activity and the oil was more effective in potentiating the activity of conventional antibiotics.